Optimization of soybean physiochemical, agronomic, and genetic responses under varying regimes of day and night temperatures - Ding, Chuanbo; Alghabari, Fahad; Rauf, Muhammad; Zhao, Ting; Javed, Muhammad Matloob; Alshamrani, Rahma; Ghazy, Abdel-Halim; Al-Doss, Abdullah A.; Khalid, Taimoor; Yang, Seung Hwan; Shah, Zahid Hussain (Frontiers in Plant Science, 2024)
Soybean is an important oilseed crop worldwide; however, it has a high sensitivity to temperature variation, particularly at the vegetative to pod filling stage. Temperature change affects physiochemical and genetic traits regulating the soybean agronomic yield. In this regard, the current study aimed to comparatively evaluate the effects of varying regimes of day and night temperatures (T1=20/12°C, T2=25/17°C, T3=30/22°C, T4=35/27°C, T5=40/32°C) on physiological (chlorophyll, photosynthesis, stomatal conductance, transpiration, membrane damage) biochemical (proline, antioxidant enzymes), genetic (GmDNJ1,